1988
DOI: 10.1086/203669
|View full text |Cite
|
Sign up to set email alerts
|

Prehistoric Exchange Across the Vitiaz Strait, Papua New Guinea

Abstract: behaviour within the plow zone. journal of Field Archaeology II:356-63. GAFFNEY, V., AND M. TINGLE. I985. "The Maddle Farm (Berks.) Project and micro-regional analysis," in Archaeological field survey in Britain and abroad. Edited by S. Macready and F. H. Thompson, pp. 67-73. London: Society of Antiquaries. GALLANT, T. W. I986. "Background noise" and site definition: A contribution to survey methodology. Journal of Field Archaeology I3:403-I8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 0 publications
2
36
0
1
Order By: Relevance
“…What is much less certain is when this landscape was first set up. A tentative date of 900 BP can be suggested from the present slender archaeological evidence (see below) and this seems to fit in with findings from other parts of coastal Papua New Guinea (Irwin 1985, Lilley 1988).…”
Section: Past Social Landscapes In the Arawessupporting
confidence: 86%
See 2 more Smart Citations
“…What is much less certain is when this landscape was first set up. A tentative date of 900 BP can be suggested from the present slender archaeological evidence (see below) and this seems to fit in with findings from other parts of coastal Papua New Guinea (Irwin 1985, Lilley 1988).…”
Section: Past Social Landscapes In the Arawessupporting
confidence: 86%
“…There is also evidence to suggest that the broader regional system of the time was unlike that found later. Lilley's research in Siassi only found slight evidence of Lapita occupation on the Siassi island of Tuam in contrast to the abundant evidence of dense settlement in the later period (Lilley 1986). It appears that there were no specialist traders on the Siassi islands at this time.…”
Section: Past Social Landscapes In the Arawesmentioning
confidence: 89%
See 1 more Smart Citation
“…The exchange system within which the Arawe Islands sit (Fig. 2) has been well documented in both past and present, but usually from the perspective of the Siassi Islands and other areas to the west (Harding 1967, Lilley 1988. No one doubts that the Siassi system of trade and life was dependent on the sea.…”
mentioning
confidence: 99%
“…Considerable modifications to insular mammal assemblages via prehistoric translocations have been documented for Melanesia. We removed translocated species from island inventories; translocation was documented through the sudden appearance of a species in an island's fossil record and/or via anthropology or genetic studies: Egloff (1975), Koopman (1979), Lilley (1986), Flannery et al (1988), Flannery and Wickler (1990), Flannery and White (1991), Flannery (1993, 1995a, Leavesley and Allen (1998), Williams (1999), Heinsohn (2003), Helgen and Flannery (2004b), White (2004), Summerhayes (2007), Heinsohn (2010), and Macqueen et al (2010). However, the fossil record is extremely sparse (Flannery 1995a), and it was not possible to confirm every island population of each species as being natural or translocated.…”
Section: Biogeography Of Northern Melanesian Mammalsmentioning
confidence: 99%